PTU-157 Her2 Positivity in upper Gastrointestinal Tumours in a Large Multi-Centre UK Cohort Identifies Similar Positivity Rates but different Trends than Previously Reported and Suggests new Potential Avenues for her2 Therapies. (4th June 2013) - Butt, M A; Gandy, M; Haidry, R J; Bloom, E S; Mackie, S; Khan, M S; Louis-Auguste, J; Oukrif, D; Khan, S-U-R; Saraswati, R; Banks, M R; Rodriguez-Justo, M; et al.
Abstract : Introduction: Evaluation of HER2 status is standard practise for people with inoperable locally advanced or recurrent and/or metastatic adenocarcinoma of the stomach or gastroesophageal junction (GOJ). HER2 positivity is defined as a histology score of 3+, or 2+ with HER2 gene amplification. This study analysed gastroesophageal HER2 testing in UCL-AD over the past 2.5 years. Methods: All referrals for HER2 testing (n = 844) were reviewed. Data was captured for age (n = 367), sex (n = 320), tumour origin (n = 104), referring lab (n = 768), sample adequacy, HER2 grading (0–3+) and tumour type. Sections were immunostained with the Roche Tissue Diagnostics Pathway HER2 assay. For cases scoring 2+, F/DDISH testing was performed and the turn-around-time (TAT) from receipt to result analysed. Results: Cases were received from 61 labs, mean age 63yo (26–93yo, SD = 13) and the majority were men (71.5%). Specimens originated from oesophageal (OE) (33.7%), GOJ (13.5%), stomach (48%) and UGI metastases (4.8%). The majority (98.7%, n = 833) were HER2-graded. The tumour types were intestinal (INT) (49.6%, n = 257), diffuse (D) (29%, n = 150), mixed D/INT (14.3%, n = 74), carcinoma-in-situ (HGD/IMC) (6.4%, n = 33), squamous (Sq) and adenosquamous (ASq) (0.4%, n = 2 each). HER2 scores were 0 (44%, n = 366), 1+ (14.5%, n = 121), 2+ (18.8%, n = 156) and 3+ (22.7%, n = 189).Gene amplification of 2+ cases identified 124 (79.5%) negative, 23 (14.7%) positive and 9 (1.1%) unrecordable results. HER2 positivity (3+/2+&F/DDISH+) was noted in 10% (15/150) of D, 30.4% (78/257) of INT, 13.5% (10/74) of mixed D/INT, 54.5% (18/33) of HGD/IMC and in 50% (1/2) of Sq tumours. A TAT of < 5days was achieved in 97% of cases not requiring in situ, and < 10days in 97.5% requiring F/DDISH. Conclusion: Overall HER2-positivity rate was 25.8% in a cohort twice the size of the UK cohort reported in the benchmark ToGA trial. When compared with ToGA, subgroup analysis showed comparable but higher rates in D cancers (10% vs 6.1%), lower in both INT/mixed cancers (30.4/13.5% vs 32.2/20.4%), showed opposite proportions of GOJ/stomach cancers (28.6/31.3% vs 33.1/20.9%), and grouping proximal (OE+GOJ) cancers together, a higher ratio compared to stomach cancers was seen (0.51 vs 0.33). Positivity in Sq cancer is of uncertain significance and warrants further research into new potential applications for HER2 targeting. Disclosure of Interest: None Declared